Effects of SO2 on the quality of Barlinka and Waltham Cross grapes and the evaluation of ion chromatography for the analysis of residual sulphite - Taylor, M. A.(Martin Anthony) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.